Regressing SARS-CoV-2 Sewage Measurements Onto COVID-19 Burden in the Population: A Proof-of-Concept for Quantitative Environmental Surveillance - Bar-Or, Itay; Yaniv, Karin; Shagan, Marilou; Ozer, Eden; Weil, Merav; Indenbaum, Victoria; Elul, Michal; Erster, Oran; Mendelson, Ella; Mannasse, Batya; Shirazi, Rachel; Kramarsky-Winter, Esti; et al. (Frontiers in Public Health, 2022)
SARS-CoV-2 is an RNA virus, a member of the coronavirus family of respiratory viruses that includes SARS-CoV-1 and MERS. It has had an acute and dramatic impact on health care systems, economies, and societies of affected countries during the past eight months. Widespread testing and tracing efforts are being employed in many countries in attempts to contain and mitigate this pandemic. Recent data has indicated that fecal shedding of SARS-CoV-2 is common, and that the virus RNA can be detected in wastewater. This indicates that wastewater monitoring may provide a potentially efficient tool for epidemiological surveillance of SARS-CoV-2 infection in large populations at relevant scales. In particular, this provides important means of (i) estimating the extent of outbreaks and their spatial distributions, based primarily on in-sewer measurements, (ii), managing the early-warning system quantitatively and efficiently, and (iii) verifying disease elimination. Here we report different virus concentration methods using PEG, alum or filtration techniques as well as different RNA extraction methodologies, providing important insights regarding detection of SARS-CoV-2 RNA in sewage. Virus RNA particles were detected in wastewater in several geographic locations in Israel. In addition a correlation of virus RNA concentration to morbidity was detected in Bnei-Barak city during April 2020. This study presents a proof of concept for the use of direct raw sewage associated virus data, during the pandemic in the country as a potential epidemiological tool.